Cyclopropenation of internal alkynylsilanes and diazoacetates catalyzed by copper(i) N-heterocyclic carbene complexes. Issue 5 (7th January 2016) - Thomas, Thomas J.; Merritt, Benjamin A.; Lemma, Betsegaw E.; McKoy, Adina M.; Nguyen, Tri; Swenson, Andrew K.; Mills, Jeffrey L.; Coleman, Michael G.
Abstract : Copper(i ) N-heterocyclic carbene (CuNHC) complexes are effective catalysts for the cyclopropenation of internal alkynylsilanes and diazoacetates compounds. Abstract : Copper(i ) N-heterocyclic carbene (CuNHC) complexes are more catalytically active than traditional transition metal salts for the cyclopropenation of internal alkynylsilanes and diazoacetate compounds. A series of 1, 2, 3-trisubstituted and 1, 2, 3, 3-tetrasubstituted cyclopropenylsilane compounds were isolated in good overall yields. An interesting regioselective and chemodivergent reaction pathway was also observed to furnish a tetra-substituted furan for an electron-rich donor/acceptor diazoacetate. Finally, a practical synthesis of a cyclopropenyl-containing starting material that is useful for bioorthogonal chemistry is also described.